Cool shades : the history and meaning of sunglasses - Gill-Brown, Vanessa, 1970- (Bloomsbury Academic, 2015)
"Cool Shades provides the first in-depth exploration of the enduring appeal of sunglasses in visual culture, both historically and today. Ubiquitous in fashion, advertising, film and graphic design, sunglasses are the ultimate signifier of 'cool' in mass culture; a powerful attribute pervading much fashion and pop cultural imagery which has received little scholarly attention until now. Accessible and highly engaging, this book offers an original history of how sunglasses became a fashion accessory in the early twentieth century, and addresses the complex variety of meanings they have the power to articulate, through associations with vision, light, glamour, darkness, fashion, speed and technology in the context of modernity. Cool Shades will be of great interest to students of fashion, design, visual and material culture, cultural studies and sociology, as well as general readers fascinated by this iconic fashion staple"--